Probabilistic approach to the analysis of regularities in behavior of material parameters of electronic equipment under action of external fields - Milenin, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
It has been shown that the dependence between the parameters of materials of electronic equipment and external fields is determined by the distribution function of the corresponding random variable. The obtained results have been applied to the analysis of a number of physical phenomena.